Peningkatan Minat dan Kesiapan Akademik Siswa melalui Simulasi Edukatif Budi Luhur College - Rizka Tiaharyadini; Zaqi Kurniawan; Windhy Widhyanty (Ikatan Ahli Informatika Indonesia, 2025)
The transition from high school to higher education is a critical phase that demands academic readiness, mental preparedness, and strong student motivation. However, many high school students still have limited understanding of university life and the realities of the academic process. The lack of exposure to campus environments contributes to low motivation and inadequate preparation for continuing their studies, highlighting the need for a more contextual and interactive educational approach. In response, the Budi Luhur College 2025 program was designed to provide direct experience through lecture simulations, computer laboratory practicums, and faculty excursions. The program engaged 160 Grade XI students from SMA Budi Luhur, conducted over 14 sessions from February 14 to May 30, 2025. Evaluation results showed a significant increase in student satisfaction, with the number of students rating the program as “good/very good” rising from 38 at the beginning to 47 by the end. Additionally, 82% of participants reported improved understanding of campus life, and 75% stated they felt more prepared to pursue higher education. The most influential satisfaction factors were direct lecture experience (31.2%) and faculty excursions (31.2%). These findings suggest that the participatory and simulation-based approach used in the program is effective in enhancing students’ academic orientation and motivation. This success presents opportunities for future program expansion, either as an annual institutional initiative or as a sustainable collaborative community service model.